The representation of space and landscape on videogame screens: possibilities for geography education - Carneiro, Eduardo Lorini; Backes, Luciana (Geografares, 2018)
Electronic games are part of everyday life in society. Although often treated as leisure objects, they can contribute to the understanding of geographical themes such as space and landscape. The article discusses the potentiality of these artifacts for the construction of knowledge in this discipline. We present the analyzes of the pedagogical practice performed with classes of Elementary and High School of a public school exploring different electronic games to develop the concepts of Geography. In the process of interaction between students and different scenarios, there is the appropriation of these spaces, perceiving their landscapes and establishing relationships between knowledge and the context explored.